(untitled) - Higgins, Ryan T. (Los Angeles, 2025)
Norman the porcupine leaves his best friend Mildred the tree and sets out to find an adventure, but eventually decides that the best adventures are shared.
Keywords: Trees; Fiction; Voyages and travels; Fiction; Friendship; Fiction; Fiction; Fiction; Adventure and adventurers; Best friends; Adventure stories; Friendship; Juvenile fiction; Fiction; Juvenile fiction; Best friends; Juvenile fiction; Voyages and travels; Juvenile fiction; Trees; Juvenile fiction; Porcupines; Porcupines; Picture books; Animal fiction